2016
DOI: 10.7287/peerj.preprints.2517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why to choose Random Forest to predict rare species distribution with few samples in large undersampled areas? Three Asian crane species models provide supporting evidence

Abstract: Species distribution models (SDMs) have become an essential tool in ecology, biogeography, evolution, and more recently, in conservation biology. How to generalize species distributions in large undersampled areas, especially with few samples, is a fundamental issue of SDMs. In order to explore this issue, we used the best available presence records for the Hooded Crane (Grus monacha, n=33), White-naped Crane (Grus vipio, n=40), and Black-necked Crane (Grus nigricollis, n=75) in China as three case studies, em… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Random forests and boosted regression trees, two data-driven approaches that are relatively immune to overfitting and can handle predictor interactions, can demonstrate high performance in unsampled areas (e.g., [56] [8]. In recent years, dynamic models capable of tracking the temporal aspects of a species' behavior and distribution, and joint species distribution models designed to simultaneously account for the co-occurrence of multiple species, have also gained traction.…”
Section: Do Specific Modeling Approaches Results In Better Transferabimentioning
confidence: 99%
See 1 more Smart Citation
“…Random forests and boosted regression trees, two data-driven approaches that are relatively immune to overfitting and can handle predictor interactions, can demonstrate high performance in unsampled areas (e.g., [56] [8]. In recent years, dynamic models capable of tracking the temporal aspects of a species' behavior and distribution, and joint species distribution models designed to simultaneously account for the co-occurrence of multiple species, have also gained traction.…”
Section: Do Specific Modeling Approaches Results In Better Transferabimentioning
confidence: 99%
“…Random forests and boosted regression trees, two data-driven approaches that are relatively immune to overfitting and can handle predictor interactions, can demonstrate high performance in unsampled areas (e.g., [56]). MaxEnt, another machine learning method, has been ranked the most transferable in some studies (e.g., [57]).…”
Section: Do Specific Modeling Approaches Results In Better Transferabimentioning
confidence: 99%
“…We performed correlative models for each species and database (i.e., three SDMs per species) using the Random Forest algorithm (RF: Breiman, ) which is considered to be among the best performing machine learning methods (Cutler et al., ; Mi, Huettmann, Guo, Han, & Wen, ). The chosen predictors were mean annual precipitation and mean annual temperature for terrestrial mammals, and bathymetry (from MARSPEC) and sea surface temperature for marine mammals.…”
Section: Methodsmentioning
confidence: 99%
“…Range maps have been previously used in amphibian biogeographical studies at large spatial scales (McKnight et al 2007, Buckley and Jetz 2008, Lawler et al 2009), and recent findings showed a strong agreement between SDMs trained with IUCN range maps and SDMs trained with true occurrences (Fourcade 2016). Random forests are machine learning algorithms based on classification of regression trees returning the class that is the mode of the classes output by individual trees (Breiman 2001); they have been widely used in SDMs, and proven to be effective for predictive modelling (Prasad et al 2006, Mi et al 2017. Random forest classifiers are robust to over-fitting but tend to better fit the observed data than other algorithms, and hence producing more accurate predictions of species' ranges (Lawler et al 2006).…”
Section: Species Distribution Modellingmentioning
confidence: 99%